ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMA PADA MATERI KOPERASI - Wahyu Mustajab; Syamsul Hadi Senen; Ikaputera Waspada (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
Critical thinking is a way of thinking by knowing and analyzing things to get a solution. Critical thinking skills applied in students to learn to solve problems / problems. This study aims to determine the ability of critical thinking of high school students in cooperative material in class X. The method used in this research is descriptive method. Subjects in this study are high school students of class X in Kabupaten Ciamis. The sample used is 93 students, consisting of 3 classes of 32 students from IIS 1, 27 students from IIS 2 and 34 students from IIS 3. The research instrument used is about knowledge about cooperative material which amounts to 25 choices double with four alternative answer choices, the questions used are arranged according to critical thinking indicator with C4-C6 cognitive level. Data analysis used is quantitative descriptive analysis. the average of students' critical thinking early ability is 49.35% (Low) or in the low category. The low initial ability of critical thinking makes the researcher assume that students are not used to get the problem with cognitive level of C4-C6 on cooperative material. So it is necessary to do better coaching to improve students' critical thinking skills. In addition, students are also required or accustomed in solving problems with high levels of cognitive C4-C6 or cognitive level.